Environmental Crime and the Resistance of Female Forest Rangers: A Green Cultural Criminology Analysis of Mpu Uteun - Nasywa Ghaliza Medinyssa; Vinita Susanti (International Journal Labs, 2026)
Environmental crime poses a serious threat to ecosystems and local communities. This article examines Mpu Uteun's resistance as a female ranger group againts environmental crimes in the Damaran Baru Forest, Bener Meriah, Aceh, through the perspective of green cultural criminology and ecofeminism. The analysis used qualitative approach, by conducting FGDs interviews with Mpu Uteun members and observation of areas within the scope of Mpu Uteun's work. This article reveals how Mpu Uteun members interpreted their actions as an effort to enforce of socio-ecological values while confronting the local patriarchal culture. The findings show that Mpu Uteun members made efforts to prevent environmental crimes through forest patrol strategy, which in turn expose them to cultural resistance. This article concludes that the integration of green cultural criminology and ecofeminism perspectives complements the understanding of environmental crime as a socio-cultural phenomenon, and contributes to policies aimed at empowering female nomadic communities.